RELIGIOUS VOLUNTARISM IN THE YOUTH MUSLIM PHYLANTROPIC MOVEMENT IN MEDAN - Sahran Saputra; Nirwansyah Putra (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2021)
This research discusses religious voluntarism in the philanthropic movement carried out by the Muslim youth hijrah community. The purpose of this study is to find out how the patterns of voluntarism in the philanthropic movement of Muslim youth in Medan. This research uses qualitative methods with data collection techniques through observation, interviews, and literature study. The results of this study indicate that the idea of the movement carried out by young Muslims is based on the religiosity of the activists, as a spiritual response to the social and spiritual conditions of Muslim youth in Medan City. Hijrah community recruits volunteers on a voluntary basis, his motivation is to improve himself to be pious individually and socially by returning to religious teachings according to the guidance of the Qur'an and Hadith. Building Islamic values as a spirit of migration into commitment and shared values of the organization and all its managers. These organizational values and commitments lead to the spirit of religious voluntarism.Keywords : religious voluntarism, the hijrah movement, Muslim youth